THE MAKING OF DUAL PHASE STEEL WITH DOUBLE STEP ANNEALING METHOD - DZIKRI AHIRA SOEFIHARA (NIM: 12513010), M.
Over the last 3 decades, the use of high-strength steel in the automotive industry has reduced the weight of material used for vehicles by 25% - 40% while maintaining strength therefore reduce the usage of energy and exhaust consumption. One of the most widely used advanced high-strength steel (AHSS) types is dual phase steel. The dual phase steel is composed of a soft ferrite matrix and a hard martensite island matrix therefore the double phase steel has an excellent combination of strength and ductility. The combination of appropriate variations of heat treatment and temperatur needed to obtain dual phase steel with suitable microstructure to have good mechanical properties. Preparation of dual phase steel in this research was carried out by heating API 5L X65 steel to intercritical annealing (IA) temperature followed by rapid cooling with water. This research started with sample preparation of low carbon steel API 5L X65 processed by hot rolling from PT Krakatau Steel. Furthermore, the steel machined to become 13 tensile test samples according to ASTM E8 standard consisting of 1 as received specimen, 4 specimens for intercritical annealing (IA) treatment, and 8 specimens for double step annealing (DSA) treatment. The steel is subjected to variations of heat treatment at temperature of 800°C, 820°C, 840°C, and 860 °C in the first IA and at a temperature 760°C and 780°C in the second IA. Characterizations are done by tensile test, hardness measurement, optical microscope observation, and observation by scanning electron microscope (SEM). The data is further processed to obtain the effect of heat treatments and IA temperatur variations on the microstructure, fracture and the properties of the resulting dual phase steel. Dual phase steel of IA heat treatment resulted an equiaxed martensite microstructure surrounded by a ferrite phase whereas the dual phase steel of the DSA heat treatment resulted a networked martensite microstructure surrounding the ferrite phase. Fractures resulting from both heat treatment IA and DSA exhibit characteristic of ductile fracture with equally distributed dimple. The highest martensite volume of 38,2% was obtained in the variation of IA 860°C. The highest values of tensile strength and hardness were 747,9 MPa and 383,1 HV, respectively, which were obtained in variation of IA 860°C. The highest elongation, toughness, and strain hardening exponent were 25,68%, 332,8 MPa, and 0,36, respectively, which were obtained in variation of DSA 820°C-760°C. The higher martensite volume will increase tensile strength and hardness while elongation, toughness and strain hardening exponent will decrease. Characteristics shown by dual phase steel in this study are continuous yielding behavior and low YS/TS ratio.